The Cardioprotective Potential of Herbal Formulas in Myocardial Infarction-Induced Heart Failure through Inhibition of JAK/STAT3 Signaling and Improvement of Cardiac Function - Youn-Jae Jang; Hye-Yoom Kim; Se-Won Na; Mi-Hyeon Hong; Jung-Joo Yoon; Ho-Sub Lee; Dae-Gill Kang (MDPI AG, 2024)
Myocardial infarction (MI) is a leading cause of heart failure, characterized by adverse cardiac remodeling. This study evaluated the cardioprotective potential of Dohongsamul-tang (DHT), a traditional Korean herbal formula, in a rat model of MI-induced heart failure. Rats underwent left anterior descending (LAD) artery ligation and were treated with either 100 mg/kg or 200 mg/kg of DHT daily for 8 weeks. DHT treatment significantly improved cardiac function, as evidenced by increased ejection fraction (EF) from 62.1% to 70.1% (100 mg/kg) and fractional shortening (FS) from 32.3% to 39.4% (200 mg/kg) compared to the MI control group. Additionally, DHT reduced infarct size by approximately 63.3% (from 60.0% to 22.0%) and heart weight by approximately 16.7% (from 3.6 mg/g to 3.0 mg/g), and significantly decreased levels of heart failure biomarkers: LDH was reduced by 37.6% (from 1409.1 U/L to 879.1 U/L) and CK-MB by 47.6% (from 367.3 U/L to 192.5 U/L). Histological analysis revealed a reduction in left ventricle (LV) fibrosis by approximately 50% (from 24.0% to 12.0%). At the molecular level, DHT inhibited the expression of phospho-JAK by 75% (from 2-fold to 0.5-fold), phospho-STAT3 by 30.8% (from 1.3-fold to 0.9-fold), Bax/Bcl-2 by 56.3% (from 3.2-fold to 1.4-fold), and caspase-3 by 46.3% (from 1.23-fold to 0.66-fold). These results suggest that DHT exerts cardioprotective effects by modulating the JAK/STAT3 signaling pathway, highlighting its potential as a therapeutic option for heart failure.